Analyzing Coping Mechanisms in â€œThe Whaleâ€: Charlie and Ellieâ€™s Psychological Realism - Yosephine Flowrina Sumitro; Maria Vincentia Eka Mulatsih (Universitas Muhammadiyah Tangerang, 2025)
This study examines real-life mental health which is coping mechanism in â€œThe Whaleâ€ film. It addresses two issues, namely: coping mechanisms Charlie and Ellie employ and the differences of their coping mechanisms which impact their individual quests for a better life. This study employs document analysis and a psychological approach to coping mechanisms based on Lazarus and Folkman's model. Stuart and Sundeen further categorize as adaptive and maladaptive. The researchers find that maladaptive coping dominates both characters, leading to Charlie's health problems and Ellie's academic failure. The film ends with Charlie dying due to health issues, so the positive connection with Ellie comes too late. Meanwhile, Ellie, who dislikes school, still aspires to graduate but fails. Their quest for a better life hinges on being able to confront them in healthier ways. The study concludes that relying on unhealthy coping methods hinders a better life.